A thousand and one ingredients: Medieval Arab cuisines rich heritage - United Nations Educational, Scientific; Cultural Organization; Daniel Newman (The UNESCO Courier, 2025)
As the central hub of a vast network of civilizations, the medieval Muslim-Arab world left a legacy of recipes and cooking techniques that continue to impact global food traditions today.